Nghiên cứu thực nghiệm áp dụng bản tin VOA SPECIAL ENGLISH trong dạy kỹ năng nói trong thuyết hành vi =A case study of teaching through VOA SPECIAL ENGLISH in ligh of beha viourism theory /Võ Duy Đức. - Võ, Duy Đức.
The paper examines how VOA Special English program helps first – year English majors at Quy Nhon University improve their speaking skill and investigates their attiude towards the use of this program in speaking classes.The study draws on the theories of behaviorism and text- based language teaching with the deployment of qualitative and qualitative and quantitative methods for the data analysis. The findings show that the participants benefited from VOA SE; however, some considerations should be taken into account if this program is added to the speaking syllabus.